Brothers of the gun : Wyatt Earp, Doc Holliday, and a reckoning in Tombstone - Gardner, Mark Lee, 1960- (Dutton, 2025)
This dual biography chronicles the lives of Wyatt Earp and Doc Holliday, tracing their early experiences, friendship, and roles in law enforcement and conflict in the American West. The work examines the historical context of Dodge City, the O.K. Corral gunfight, and subsequent events, using primary sources such as letters, diaries, court records, and contemporary newspapers. The narrative presents both the accomplishments and flaws of Earp and Holliday, providing a detailed account of their lives and relationship without idealization.